Pengaruh Literasi Keuangan, Motivasi Investasi, Persepsi Risiko, Pengaruh Sosial, dan Modal Minimal terhadap Minat Investasi Saham pada Generasi Z - Luthfi Nur Azizah; Isnaeni Rokhayati; Dian Safitri Pantja Koesoemasari (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the influence of financial literacy, investment motivation, risk perception, social influence, and minimum capital on stock investment interest among Generation Z. The population consisted of 134 members of the Beginner Stock Investor Community in Purwokerto, and the sampling technique used was probability sampling with a simple random sampling method, resulting in 101 respondents. This research employed a quantitative approach using a survey method through the distribution of questionnaires, and the data were analyzed using multiple linear regression analysis. The results indicate that financial literacy, investment motivation, social influence, and minimum capital have a positive and significant effect on stock investment interest, while risk perception has a negative and significant effect on stock investment interest. The limitation of this study is that it was conducted only among members of the Beginner Stock Investor Community in Purwokerto, so the findings cannot be broadly generalized to all Generation Z individuals in other regions or communities with different characteristics.